Short-term Effects of Sling Exercise Combined with Massage on the Treatment of Neck Type Cervical Spondylopathy - LI Jianfei; ZHAO Hong; CHEN Qian; LI Li; ZHANG Deqi (康复学报)
Objective: To observe the effects of sling exercise combined with massage in patients with neck type cervical spondylopathy (NTCS) by using surface electromyography (sEMG), and to explore the short-term effects on neck pain, neck disabilities and muscle fatigue.MethodsA total of ninety-three patients with neck type cervical spondylopathy who met the inclusion criteria were divided into three groups according to the random number table: massage group, sling exercise group and sling exercise combined with massage group, with 31 cases in each group. The three groups were treated with massage, sling exercise, sling exercise combined with massage therapy respectively, 30 minutes per time, once a day, 5 days per week, for a total of one week. Before and after treatment, the McGill Pain Questionnaire (MPQ) and the Neck Disability Index (NDI) were used to evaluate the cervical function and quality of life of patients, and the median frequency (MF) of the upper trapezius muscle was measured by electromyography biofeedback instrument.ResultsBefore treatment, the MPQ scores, NDI scores and MF value of the three groups were not statistically different (P>0.05). After treatment, the MPQ scores, NDI scores and MF value of the three groups were all improved (P<0.05); the MPQ scores and NDI scores of the three groups all decreased, and those of the massage group, sling exercise group and sling exercise combined with massage group were (16.68±2.52) scores, (17.06±1.71) scores, (15.03±1.66) scores, and (15.35±4.77) scores, (15.29±4.38) scores, (13.71±4.61) scores respectively; the MF value increased, the value on the left was (69.73±6.47) Hz, (70.05±7.40) Hz and (73.34±5.21) Hz respectively, and the value on the right was (63.29±8.66) Hz, (63.51±9.76) Hz and (65.85±8.21) Hz respectively, the differences were statistically significant (P<0.05); the short-term effects of sling exercise combined with massage group on neck pain, dysfunction and neck muscle fatigue were better than those of the massage group and the sling exercise group respectively (P<0.05), but there were no significant differences between the massage group and the sling exercise group (P>0.05). Further correlation analysis showed that the MPQ scores was negatively correlated with MF value (left: r=-0.626, P<0.05; right: r=-0.695, P<0.05); besides the NDI scores decreased with the increase of MF value (left: r=-0.692, P<0.05; right: r=-0.491, P<0.05), and the average MF value on the right was lower than that on the left.ConclusionSling exercise combined with massage can significantly reduce the patient's pain, activate and strengthen the neck muscles, improve the neck function of patients. At the same time, the sEMG can objectively reflect that sling exercise combined with massage has better short-term effects on the upper trapezius muscle.